“Genome studies in Soybean’’ (Glycine.max.L.) - B.F. Mundhe (The Bioscan, 2025)
Soybean (Glycine max) is a vital crop for human nutrition and animal feed. Understanding the soybean genome is essential for improving its yield, quality, and disease resistance. Genome studies in soybean have accelerated in recent years, driven by advances in sequencing technologies and bioinformatics tools. The chromosome number of soybean and other diploid Glycine species is 2n=40, which is doubled relative to its phaseoloid legume relatives (e.g. Phaseolus, Vigna), most of which are 2n = 20 or 2n = 22.Soybean has 20 chromosome pairs that are derived from at least two rounds of genome wide duplication or polyploidy events although, cytogenetically, soybean behaves like a diploid and has disomic inheritance for most loci. In addition, as a diploid evolved from palaeotetraploid, soybean has a highly duplicated genome with about 75% predicted genes maintaining multiple copies, which leads to high genetic redundancy and increases the complexity of elucidating soybean gene function (Schmutz et al., 2010). Chromosomes studies in soybean were analysis carried out of 18 genotypes of soybean phenotypic coefficient of variation was slightly higher than that of genotype coefficient of variation for all the traits. Present investigation studied the chromosome behavior showed the Generally 40 chromosome in soybean but in tabacina (Labill) Benth contain 80, tomentella Hayata,78 and tomentella Hayata.33 chromosome are found The genus Glycine consists of two subgenera, Glycine and Soja (Moench) F. J. Herm. The subgenus Soja comprises the cultivated soybean G. max (L.) Merrill and its annual wild progenitor, G. soja Sieb and Zucc (also known as Gussuriensis). These two species have diploid chromosome number, 2n=40.Prior to 1983, only seven species were recognized in the subgenus Glycine.Tindale and Craven added eight new species of Glycine from northwestern Australia. The subgenus Glycine is thus, composed of 15 wild perennial species (show in Table).Out of these two species namely G. tabacina (2n=40, 80) and G. tomentella (2n=38, 40, 78, 80), are polyploidy forms, whereas the other 13 species are diploids (2n=40). Hymowitz and Singh, (1992) have assigned genome symbols to several of the species of both the subgenera.